Nantucket Pine Tip Moth, Rhyacionia frustrana (Comstock) (Insecta: Lepidoptera: Tortricidae) - Wayne N. Dixon (EDIS, 2023)
The Nantucket pine tip moth, Rhyacionia frustrana (Comstock), is a serious pest of young pine in plantations, wild pine seedlings in open areas, Christmas tree plantings, ornamental pines, and pine seed orchards in the United States. Growth loss and stem deformity, caused by larvae feeding inside growing shoots, buds, and conelets, can be considerable during the first five years when most damage occurs (Yates et al. 1981). The increasing population of a preferred host species, loblolly pine (Pinus taeda L.), in Florida poses an ever-increasing problem of Nantucket pine tip moth infestations. This document is EENY-304 (originally published as DPI Entomology Circular 298), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2003.